Change in standardized uptake values in delayed F-18-FDG positron emission tomography images in hepatocellular carcinoma - (:unkn) unknown (LIPPINCOTT WILLIAMS & WILKINS, 2018)
Delayed 18F-2-fluoro-2-deoxy-D-glucose (18F-FDG) positron emission tomography (PET) imaging has been associated with improved diagnostic yield in several malignancies; however, data on the use of delayed imaging in patients with hepatocellular carcinoma (HCC) is scarce. This study aimed to examine tumoral and background standardized uptake value (SUV) alterations in dual-phase 18F-FDG PET/computed tomography (CT) imaging. Fifty-two HCC cases underwent dual-time-point 18F-FDG PET/CT examination where early and delayed images were obtained. The maximum and mean SUVs (SUVmax and SUVmean) of the tumor were determined for both time points. Similarly, the average SUVmean were also determined for background (liver, soft tissue, and spleen). Changes in tumoral and background SUV between early and delayed images were examined. The mean age was 62.0 +/- 12.9 years (range, 20-88 years) and the majority of the patients were men (86.5%). Tumor SUVs, both tumor SUVmean and tumor SUVmax, significantly increased at delayed images when compared to early images. In contrast, the average SUVmean for the liver, soft tissue, and spleen significantly decreased at delayed images. A significant increase in tumor SUV in delayed images in contrast to a significant decrease in background SUVs suggests that delayed images in HCC may contribute to diagnostic performance through a potential increase in the contrast between the tumor and background. However, further studies with larger sample sizes including patients with benign lesions and different grades of the disease are warranted to better elucidate the diagnostic contribution as well as the association of delayed imaging values with prognosis.
Keywords: F-18-FDG positron emission tomography; delayed images; dual-phase imaging; hepatocellular carcinoma; standardized uptake value; DUAL-TIME-POINT; GLUCOSE-METABOLISM; PET; DIAGNOSIS; TUMORS; FLUORINE-18-FLUORODEOXYGLUCOSE; INJECTION; CANCER